Digital transformation in Testing, Inspection, and Certification (TIC) sector during Covid-19 and lesson learned - Kwan, Peggy Dict Shan (2022)
According to (Rogers, 2016) digital transformation is not just about technology, but about strategy and new ways of thinking. The rules of business have changed in every industry with the widespread adoption of digital technologies. The digital revolution has already created threats to companies that fail to adapt and transform in the digital era (Vaska, et al., 2021). The tremendous growth of the Internet has presented stark challenges for business. The fundamental rules and assumptions that governed and defined the growth of the businesses in the pre-digital era are no longer valid. Without adopting the changes needed for the digital age; it will not be possible for a company to continue to thrive in the future.